Comparative Study on Data Mining Algorithms for Healthcare Information System - Kumar, K. Mohan; Jamuna, S (International Journal of Computer Sciences and Engineering, 2025)
Data Mining Is A Process Using High Volume Of Data For Needful Information. Most Popular Data Mining Techniques Are Rule Mining, Clustering, Classification And Sequence Pattern. Number Of Tests Should Be Done For A Patient To Detect A Disease. So, Large Volume Of Information Is Stored By The Health Care Information System For Further Reference. Due To The Complication Of Healthcare Information And The Slow Acquisition Of Technology, This Industry Lags Behind Other Industries In Implementing Effective Data Analysis And Extraction Strategies. Mining Information From The Large Health Databases Gives The Best Healthcare Information, Reduces Time And Saves The Humans From Complicated Diseases Like Cancer. In This Circumstance Proper Data Mining Technique Is Needed For The Best Performance. This Research Work Focuses On The Advantages And Disadvantages Of Various Data Mining Prediction Algorithms